ANALISA RISIKO KESELAMATAN DAN KESEHATAN KERJA DALAM UPAYA PENCEGAHAN PENYEBARAN VIRUS COVID-19 METODE IDENTIFIKASI BAHAYA DAN PENILAIAN RESIKO (IBPR) DI AREA BATCHING PLANT PT MOTIVE MULIA - Tissa Mutia Angreni; Nur hayati (JURNAL TECHLINK, 2022)
PT Motive Mulia (Merah Putih Beton) is a subsidiary of PT Cemindo Gemilang (Semen Merah Putih), a company engaged in construction materials. The purpose of this study was to analyze potential hazards, assess risks and carry out efforts to control and apply risks to the transmission of the covid-19 virus in the Batching Plant area of PT Motive Mulia Jatiasih using the Hazard Identification Risk Assessment (IBPR) method. The identification results contained 8 findings of potential dangers that could occur in the observed transmission of the Covid-19. Worker risk results based on the calculation of the severity index of probability and impact, employee activities in the office area have an extreme risk level, the probability value of SI is 70,53 with probability level 4 and SI impact is 78,03 with impact matrix level 4. Employee activities in the field area has an extreme risk level, the probability SI score is 78,12 with a probability level of 4 and the impact SI is 72,34 with an impact matrix level 4. Efforts made to control such as installing brochures on aspects for preventing the Covid-19 virus about avoiding Covid-19 with 5 M employees. Office and field areas have complied with wearing masks and maintaining distance. In some corners of the office, sanitizers have provided to each employees. The results of the analysis in the application of health protocols to PT Motive Mulia’s workers in an effort to prevent covid-19 in the Jatiasih Plant area, workers are 100% aware of complying with health protocols by applying masks in the office area, keeping a distance of 1 meter from colleagues, washing hands before and after touching faces or objects, maintain health and employees have vaccinated.